Two sisters with Bardet-Biedl syndrome: brain abnormalities and unusual facial findings - Aksoy, Ayşe; Karagüzel, Gülay; Akbulut, Ulaş; Türk, Adem (The Turkish Journal of Pediatrics, 2011)
Bardet-Biedl syndrome (BBS) is a rare autosomal recessive disorder with a wide spectrum of clinical manifestations. BBS is predominantly characterized by dysmorphic distal extremities, obesity, structural abnormalities or functional impairment of the kidney, rod cone dystrophy, and varying degrees of mental retardation. Hypogenitalism is also present, only in males, and in all cases, facial similarities. We present herein two sisters with BBS, one of whom also had cerebellar vermis hypoplasia and cerebral and cerebellar atrophy, and both of whom had ocular abnormalities in the form of epicanthus and telecanthus and metabolic syndrome. It should also be emphasized that the occurrence of cerebellar involvement such as cerebellar vermis hypoplasia and cerebellar atrophy in BBS is very unusual. The association of abnormalities in brain development and other facial features in children with BBS is not seen frequently; thus, these abnormalities should be searched carefully.